Dampak Promosi Gratis Ongkos Kirim Terhadap Keputusan Pembelian Produk di E-Commerce Shopee Pada Masa Pandemi Covid-19 - Sinari Maydena; Batrisyia, Quandizza (International Journal Administration, Business & Organization, 2021)
This study aims to determine how much influence the free shipping promo provided by Shopee ecommerce on purchasing decisions by Bandung State Polytechnic Students. The population in this study were all Shopee users who were Bandung State Polytechnic students, with a sample of this study amounting to 100 respondents. The data analysis technique used is simple regression analysis. The results showed that free promo shipping (X) had a positive influence and contributed 53% to the purchase decision (Y) of products in e-commerce Shopee